2020
DOI: 10.1111/nin.12382
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the lived experience of working with limited personal protective equipment during the COVID‐19 crisis

Abstract: Coronavirus disease 2019 (COVID‐19) has placed significant strain on United States’ health care and health care providers. While most Americans were sheltering in place, nurses headed to work. Many lacked adequate personal protective equipment (PPE), increasing the risk of becoming infected or infecting others. Some health care organizations were not transparent with their nurses; many nurses were gagged from speaking up about the conditions in their workplaces. This study used a descriptive phenomenological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
123
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(133 citation statements)
references
References 40 publications
10
123
0
Order By: Relevance
“…While loss was prominent, and an inevitable part of sacrifice, nurses also shared accounts of how their professional identity and practice were positively impacted, thus pointing to possibilities for gain to co-exist alongside loss. Similar to other COVID-19 research ( Iheduru-Anderson, 2020 ; Sun et al., 2020 ), nurses in our study shared feelings of fear, isolation, anger, and frustration. They recounted how unrelenting fears of contracting the virus and infecting others drove them to sacrifice seeing family and friends.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…While loss was prominent, and an inevitable part of sacrifice, nurses also shared accounts of how their professional identity and practice were positively impacted, thus pointing to possibilities for gain to co-exist alongside loss. Similar to other COVID-19 research ( Iheduru-Anderson, 2020 ; Sun et al., 2020 ), nurses in our study shared feelings of fear, isolation, anger, and frustration. They recounted how unrelenting fears of contracting the virus and infecting others drove them to sacrifice seeing family and friends.…”
Section: Discussionsupporting
confidence: 85%
“…As frontline providers, they spend sustained periods of time caring directly for patients and families, and working tirelessly to equip themselves with the knowledge about transmission, symptoms, diagnosis, and treatment of this novel virus. At the same time, they are dealing with many other issues involving compromised work conditions ( Thorne, 2020 ), increased workload with long hours, inadequate personal protective equipment (PPE) ( Iheduru-Anderson, 2020 ; Jackson et al., 2020 ), and a shifting knowledge base concerning COVID-19 transmission and virulence which has required them to engage in expanding their knowledge base and skill set ( Stokes-Parish et al., 2020 ).…”
Section: Background and Purposementioning
confidence: 99%
“…Changes in hospital policies made to protect babies as well as healthcare professionals and their families were compromised of human qualities of care that were fundamental to their approach to neonatal nursing. The concern of infecting one's own family is a significant and understandable concern for nurses caring for COVID-19 patients ( Galehdar et al, 2020 ; Iheduru-Anderson, 2020 ; Liu et al, 2020 ). What is notable about the experiences of neonatal nurses, in contrast to adult intensive care nurses, is the tension experienced between providing protection alongside the human quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…Non-medical staff presented higher levels of anxiety and depression than medical staff in this survey, which is also stated in a previous study ( 39 ). Potential factors contributing toward this finding include that medical staff usually have more knowledge and experience in infection control measures, and they are more likely to be equipped with adequate personal protective equipment (PPE) compared to non-medical staff ( 9 , 38 40 ). Current studies have reported that inadequate PPE, and having less pandemic knowledge and training are associated with higher levels of psychological distress ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%